Moisture sensitivity examination of asphalt mixtures using thermodynamic, direct adhesion peel and compacted mixture mechanical tests - Zhang, Jizhe; Airey, Gordon D.; Grenfell, James; Apeagyei, Alex K. (Taylor & Francis, 2018)
Moisture damage in asphalt mixtures is a complicated mode of pavement distress that results in the loss of stiffness and structural strength of the asphalt pavement layers. This paper evaluated the moisture sensitivity of different aggregate–bitumen combinations through three different approaches: surface energy, peel adhesion and the Saturation Ageing Tensile Stiffness (SATS) tests. In addition, the results obtained from these three tests were compared so as to characterise the relationship between the thermodynamic and the mechanical tests. The surface energy tests showed that the work of adhesion in dry conditions was bitumen type dependent, which is in agreement with the peel test. After moisture damage, all of these three tests found that the moisture sensitivity of aggregate–bitumen combinations were mainly aggregate type dependent. Based on the peel test, the moisture absorption and mineralogical compositions of aggregate were considered as two important factors to moisture sensitivity. This phenomenon suggests that in a susceptible asphalt mixture, the effect of aggregate may be more influential than the effect of bitumen. The SATS test and the peel test showed similar moisture sensitivity results demonstrating the good correlation between these two mechanical tests. However, the surface energy tests and the mechanical tests cannot correlate in terms of moisture sensitivity evaluation.